Autoinducer 2 Signaling via the Phosphotransferase FruA Drives Galactose Utilization by Streptococcus pneumoniae, Resulting in Hypervirulence - Claudia Trappetti (American Society for Microbiology, 2017)
ABSTRACT Communication between bacterial cells is crucial for the coordination of diverse cellular processes that facilitate environmental adaptation and, in the case of pathogenic species, virulence. This is achieved by the secretion and detection of small signaling molecules called autoinducers, a process termed quorum sensing. To date, the only signaling molecule recognized by both Gram-positive and Gram-negative bacteria is autoinducer 2 (AI-2), synthesized by the metabolic enzyme LuxS (S-ribosylhomocysteine lyase) as a by-product of the activated methyl cycle. Homologues of LuxS are ubiquitous in bacteria, suggesting a key role in interspecies, as well as intraspecies, communication. Gram-negative bacteria sense and respond to AI-2 via the Lsr ABC transporter system or by the LuxP/LuxQ phosphorelay system. However, homologues of these systems are absent from Gram-positive bacteria and the AI-2 receptor is unknown. Here we show that in the major human pathogen Streptococcus pneumoniae, sensing of exogenous AI-2 is dependent on FruA, a fructose-specific phosphoenolpyruvate-phosphotransferase system that is highly conserved in Gram-positive pathogens. Importantly, AI-2 signaling via FruA enables the bacterium to utilize galactose as a carbon source and upregulates the Leloir pathway, thereby leading to increased production of capsular polysaccharide and a hypervirulent phenotype. IMPORTANCE S. pneumoniae is a Gram-positive bacterium frequently carried asymptomatically in the human nasopharynx. However, in a proportion of cases, it can spread to other sites of the body, causing life-threatening diseases that translate into massive global morbidity and mortality. Our data show that AI-2 signaling via FruA promotes the transition of the pneumococcus from colonization to invasion by facilitating the utilization of galactose, the principal sugar available in the upper respiratory tract. AI-2-mediated upregulation of Leloir pathway enzymes results in increased production of capsular polysaccharide and hypervirulence in a murine intranasal challenge model. This identifies the highly conserved FruA phosphotransferase system as a target for new antimicrobials based on the disruption of this generic quorum-sensing system.